Hubungan Bimbingan Orang Tua Dengan Motivasi Belajar Pendidikan Agama Islam Siswa SDIT Rabbani Rajeg Kabupaten Tangerang - Zubairi Zubairi; Nurdin Nurdin; Tiara Zain Halida (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to investigate the relationship between parental guidance and the motivation to study Islamic Religious Education of students at SDIT Rabbani Rajeg, Tangerang Regency. The research method used is a quantitative research method using a questionnaire as a data collection instrument. The research sample consisted of students at SDIT Rabbani who were selected by simple random sampling. In this study there is a positive and meaningful relationship between parental guidance and student learning motivation (specifically in Islamic Religion subjects), the contribution of x to y is shown by a correlation coefficient of 0.951 with a coefficient of determination of 90%. This means that parents contribute 90% of the learning motivation of SDIT Rabbani students. The sample in this research, the authors determined 40 students out of a total of 153 students. Based on research from Suharsimi Arikunto, namely: "If the subject is less than 100, it is better to take all of them, if the subject is large it can be taken between 10 - 15%, or 20 - 25% or more. 5 The author took a sample of 40 students from 153 students at SDIT Rabbani. The sample technique chosen is random sample or simple random sample. Thus it can be concluded that parental guidance can significantly determine student learning motivation. The results showed that there was a significant relationship between parental guidance and the motivation to study Islamic Religious Education for SDIT Rabbani students. Data analysis revealed that the level of guidance given by parents was positively related to the level of students' learning motivation in dealing with Islamic Religious Education subjects. This research makes an important contribution to the understanding of the role of parents in increasing students' motivation to study Islamic Religious Education. The results of this study indicate that the support, guidance, and attention given by parents can influence students' motivation in learning Islam. Therefore, it takes an active and involved role from parents in providing proper guidance in learning Islam to their children.